Meningkatkan Motivasi dan Loyalitas Karyawan UMKM Enaxmen Boga Rasa Semarang dengan Program Kemitraan - Masine Slahanti; Nisa Novia Avien Christy; Enggar Dhian Pratamanti (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
MSMEs play a role in improving the welfare of the wider community, as well as improving the national economy. In the Indonesian economy, MSMEs are the business group with the largest number and have been proven to be able to withstand various kinds of economic crisis shocks. The development of MSMEs receives support from various parties, where the government and elements of society help develop and improve MSMEs so that people who own these businesses can improve their economy, and academics also contribute by providing or holding activities, counseling and training aimed at increasing success and improving the economy for business owners. One of the MSMEs in Semarang is engaged in milkfish processing. The owner, Mrs. Kurniawati, has a milkfish processing business with the brand "EnaXmen Boga Rasa." A home industry business located in Semarang. Currently, the obstacles faced by business owners are employees coming in and out and when they leave they create a similar business after they understand the process. This Community Service production will provide increased understanding of managing Human Resources, especially in providing motivation to employees by treating them as partners with the hope that employees can have loyalty in working without going in and out and of course as business owners can focus more on developing their business in the present and future. come